Rethinking empowerment : gender and development in a global/local world - Parpart, Jane L.; Rai, Shirin; Staudt, Kathleen A.; University of Warwick. Centre for the Study of Globalisation and Regionalisation (London : Routledge, 2002)
'Rethinking Empowerment' looks at the changing role of women in developing countries and rejects the established notion that empowerment in development is best understood and pursued at a local/global level
At foot of title : Centre for the Study of Globalisation and Regionalisation
Includes bibliographical references and index
Keywords: Women -- Developing countries -- Social conditions; Women in development -- Developing countries